Integrated community-based reporting and field diagnostics for improved rabies surveillance in rural Laikipia, Kenya - Odinga, Christian O.; Thomas, Lian F.; Wambugu, E.; Ferguson, A.W.; Fèvre, Eric M.; Gibson, A.; Hassell, James M.; Muloi, Dishon M.; Murray, S.; Surmat, A.; Mwai, P.M.; Woodroffe, R.; et al. (Wiley, 2025)
Rabies vaccination in domestic dog populations has increased globally in a bid to protect human health. Surveillance efforts, however, are inconsistent in endemic regions such as in sub-Saharan Africa, due to fragmented reporting and limited diagnostic capacity for suspected cases, limiting successful monitoring and evaluation of vaccination campaigns. Here, we conducted a pilot study aiming to strengthen rabies surveillance by combining community-based surveillance with field-based diagnostic testing in pastoral and agro-pastoral communities in central Kenya; communities which are frequently marginalised from health systems. During the 6-month pilot study, there were 14 alerts of suspected rabid dogs in the community, of which eight were tested and five diagnostically confirmed as rabid. Two positive samples processed successfully for whole genome sequencing indicated that the rabies variant circulating in central Kenya during the study period belonged to the Africa 1b subclade, which is similar to variants identified in eastern Kenya and Tanzania, suggesting regional transmission. This pilot study indicates that rabies continues to circulate in the region and that community-based surveillance, when combined with enhanced diagnostic testing, can help alleviate underreporting and guide vaccination campaigns.